Is Delivery Killing Dine-In Restaurants?" - Eine ökonometrische Analyse von Spillover-Effekten für digitale Plattformen in der Restaurantindustrie - Philipp, Schumann

Eine strategische Analyse von Online-Kundenrezensionen zur Identifikation von Begeisterungsfaktoren mittels Latent Dirichlet Allocation - Kittsteiner, Anna Verena

Disziplin Schreibwissenschaft? Kritische Überlegungen zur Entwicklung einer „Practical Art“ - Girgensohn, Katrin; Haacke, Stefanie; Karsten, Andrea (Schreibwissenschaft - eine neue Disziplin: Diskursübergreifende Perspektiven)
Formiert sich eine Disziplin „Schreibwissenschaft“? Wir versuchen, die Form, den Gegenstand und mögliche Ziele des Feldes zu beschreiben, aus dem sich aktuell so etwas wie eine Disziplin zu bilden scheint. Nach einer Vergewisserung, was in der Wissenschaftssoziologie überhaupt unter Disziplin verstanden wird, arbeiten wir Spezifika einer Schreibwissenschaft als einer Practical Art heraus und diskutieren dann, welche Türen sich mit der Institutionalisierung einer Disziplin möglicherweise öffnen werden und welche sich vielleicht schließen.

Der Schreibprozess als Dialog. Eine Perspektive am Schnittpunkt von dialogischer Sprachwissenschaft und soziokultureller Psychologie - Karsten, Andrea (Schreibforschung interdisziplinär)

Oxidation/reduction cycles and their reversible effect on the dipole formation at CuInSe2 surfaces - Elizabeth, Amala; Sahoo, Sudhir K.; Lockhorn, David; Timmer, Alexander; Aghdassi, Nabi; Zacharias, Helmut; Kühne, Thomas; Siebentritt, Susanne; Mirhosseini, Hossein; Mönig, Harry (Phys. Rev. Materials)
The defect-electronic properties of {112} microfaceted surfaces of epitaxially grown CuInSe2 thin films are investigated by scanning tunneling spectroscopy and photoelectron spectroscopy techniques after various surface treatments. The intrinsic CuInSe2 surface is found to be largely passivated in terms of electronic defect levels in the band-gap region. However, surface oxidation leads to an overall high density of defect levels in conjunction with a considerable net surface dipole, which persists even after oxide removal. Yet, a subsequent annealing under vacuum restores the initial condition. Such oxidation/reduction cycles are reversible for many times providing robust control of the surface and interface properties in these materials. Based on ab initio simulations, a mechanism where oxygen dissociatively adsorbs and subsequently diffuses to a subsurface site is proposed as the initial step of the observed dipole formation. Our results emphasize the relevance of oxidation-induced dipole effects at the thin film surface and provide a comprehensive understanding toward passivation strategies of these surfaces.

In silico investigation of Cu(In,Ga)Se2-based solar cells - Mirhosseini, S. Hossein; Kormath Madam Raghupathy, Ramya; Sahoo, Sudhir K.; Wiebeler, Hendrik; Chugh, Manjusha; Kühne, Thomas (Phys. Chem. Chem. Phys.)
Photovoltaics is one of the most promising and fastest-growing renewable energy technologies. Although the price-performance ratio of solar cells has improved significantly over recent years{,} further systematic investigations are needed to achieve higher performance and lower cost for future solar cells. In conjunction with experiments{,} computer simulations are powerful tools to investigate the thermodynamics and kinetics of solar cells. Over the last few years{,} we have developed and employed advanced computational techniques to gain a better understanding of solar cells based on copper indium gallium selenide (Cu(In{,}Ga)Se2). Furthermore{,} we have utilized state-of-the-art data-driven science and machine learning for the development of photovoltaic materials. In this Perspective{,} we review our results along with a survey of the field.

A High-Rate Two-Dimensional Polyarylimide Covalent Organic Framework Anode for Aqueous Zn-Ion Energy Storage Devices - Yu, Minghao; Chandrasekhar, Naisa; Kormath Madam Raghupathy, Ramya; Ly, Khoa Hoang; Zhang, Haozhe; Dmitrieva, Evgenia; Liang, Chaolun; Lu, Xihong; Kühne, Thomas; Mirhosseini, S. Hossein; Weidinger, Inez M.; Feng, Xinliang (Journal of the American Chemical Society)
Rechargeable aqueous Zn-ion energy storage devices are promising candidates for next-generation energy storage technologies. However, the lack of highly reversible Zn2+-storage anode materials with low potential windows remains a primary concern. Here, we report a two-dimensional polyarylimide covalent organic framework (PI-COF) anode with high-kinetics Zn2+-storage capability. The well-organized pore channels of PI-COF allow the high accessibility of the build-in redox-active carbonyl groups and efficient ion diffusion with a low energy barrier. The constructed PI-COF anode exhibits a specific capacity (332 C g–1 or 92 mAh g–1 at 0.7 A g–1), a high rate capability (79.8% at 7 A g–1), and a long cycle life (85% over 4000 cycles). In situ Raman investigation and first-principle calculations clarify the two-step Zn2+-storage mechanism, in which imide carbonyl groups reversibly form negatively charged enolates. Dendrite-free full Zn-ion devices are fabricated by coupling PI-COF anodes with MnO2 cathodes, delivering excellent energy densities (23.9 ∼ 66.5 Wh kg–1) and supercapacitor-level power densities (133 ∼ 4782 W kg–1). This study demonstrates the feasibility of covalent organic framework as Zn2+-storage anodes and shows a promising prospect for constructing reliable aqueous energy storage devices.

Vibrational dynamics in lead halide hybrid perovskites investigated by Raman spectroscopy - Ibaceta-Jaña, Josefa; Muydinov, Ruslan; Rosado, Pamela; Mirhosseini, Hossein; Chugh, Manjusha; Nazarenko, Olga; Dirin, Dmitry N.; Heinrich, Dirk; Wagner, Markus R.; Kühne, Thomas; Szyszka, Bernd; Kovalenko, Maksym V.; et al. (Phys. Chem. Chem. Phys.)
Lead halide perovskite semiconductors providing record efficiencies of solar cells have usually mixed compositions doped in A- and X-sites to enhance the phase stability. The cubic form of formamidinium (FA) lead iodide reveals excellent opto-electronic properties but transforms at room temperature (RT) into a hexagonal structure which does not effectively absorb visible light. This metastable form and the mechanism of its stabilization by Cs+ and Br− incorporation are poorly characterized and insufficiently understood. We report here the vibrational properties of cubic FAPbI3 investigated by DFT calculations on phonon frequencies and intensities, and micro-Raman spectroscopy. The effects of Cs+ and Br− partial substitution are discussed. We support our results with the study of FAPbBr3 which expands the identification of vibrational modes to the previously unpublished low frequency region (<500 cm−1). Our results show that the incorporation of Cs+ and Br− leads to the coupling of the displacement of the A-site components and weakens the bonds between FA+ and the PbX6 octahedra. We suggest that the enhancement of α-FAPbI3 stability can be a product of the release of tensile stresses in the Pb–X bond, which is reflected in a red-shift of the low frequency region of the Raman spectrum (<200 cm−1).

Revealing the origin of the beneficial effect of cesium in highly efficient Cu(In,Ga)Se2 solar cells - Schöppe, Philipp; Schönherr, Sven; Chugh, Manjusha; Mirhosseini, Hossein; Jackson, Philip; Wuerz, Roland; Ritzer, Maurizio; Johannes, Andreas; Martínez-Criado, Gema; Wisniewski, Wolfgang; Schwarz, Torsten; T. Plass, Christian; et al. (Nano Energy)
The record conversion efficiency of thin-film solar cells based on Cu(In,Ga)Se2 (CIGS) absorbers has exceeded 23%. Such a high performance is currently only attainable by the incorporation of heavy alkali metals like Cs into the absorber through an alkali fluoride post-deposition treatment (PDT). As the effect of the incorporated heavy alkali metals is under discussion, we investigated the local composition and microstructure of high efficiency CIGS solar cells via various high-resolution techniques in a combinatory approach. An accumulation of Cs is clearly detected at the p-n junction along with variations in the local CIGS composition, showing the formation of a beneficial secondary phase with a laterally inhomogeneous distribution. Additionally, Cs accumulations were detected at grain boundaries with a random misorientation of the adjacent grains where a reduced Cu concentration and increased In and Se concentrations are detected. No accumulation was found at Σ3 twin boundaries as well as the grain interior. These experimental findings are in excellent agreement with complementary ab-initio calculations, demonstrating that the grain boundaries are passivated by the presence of Cs. Further, it is unlikely that Cs with its large ionic radius is incorporated into the CIGS grains where it would cause detrimental defects.

Animalische Epistemologie: Tierwahrheiten bei Franz Kafka am Beispiel von "Ein Bericht für eine Akademie" - Tönsing, Johanna